2021
DOI: 10.1002/admt.202000933
|View full text |Cite
|
Sign up to set email alerts
|

Direct Distinguishing of Methanol over Ethanol with a Nanofilm‐Based Fluorescent Sensor

Abstract: Methanol is extremely toxic to humans if ingested or if vapors are inhaled. Facile and reliable detection of methanol is an efficient way to reduce the risk of methanol poisoning. A great challenge in methanol detection lies in distinguishing methanol under high ethanol background. In this work, a nanofilm‐based fluorescent sensor for direct distinguishing methanol from pure ethanol or liquor is presented, where no sample pretreatment or sensor array is needed. The flexible, uniform, and amorphous nanofilm is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For example, silica-coated cellulose strips with a fluorescent chemical probe grafted to them can detect EtOH in gasoline with a 0.5 v/v% limit of detection (Gotor et al 2019). A carborane derivative film showed turn-on fluorescence whose strength and recovery rate was different for ethanol and methanol (MeOH), showing that the relative fraction of these two alcohols could be distinguished to about 1% (Han et al, 2021). Another sensor film with similar turn-on behavior also was shown in Ref.…”
Section: Introductionmentioning
confidence: 64%
“…For example, silica-coated cellulose strips with a fluorescent chemical probe grafted to them can detect EtOH in gasoline with a 0.5 v/v% limit of detection (Gotor et al 2019). A carborane derivative film showed turn-on fluorescence whose strength and recovery rate was different for ethanol and methanol (MeOH), showing that the relative fraction of these two alcohols could be distinguished to about 1% (Han et al, 2021). Another sensor film with similar turn-on behavior also was shown in Ref.…”
Section: Introductionmentioning
confidence: 64%
“…Recently in a new approach, Chakravarty et al . developed a small, electron‐rich, and twisted phenothiazine‐linked anthracene‐derived solid‐state emitter ( Probe 21 ) to recognize VOCs and organic solvents [81] . The authors reported the probe as a solvatochromic fluorophore and durable vapochromic compound, mainly in the solid‐state (Figure 17a–c).…”
Section: Probes For Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…Bazgir and co‐workers investigated imidazoisoindol‐5‐imine scaffold based fluorescent probes for methanol detection based on solvatochromism principle [15] . Miao and Fang research groups designed fluorescent nanofilm based sensor for methanol detection [16] . Effective discrimination of methanol, ethanol and propanol is reported using excited‐state intramolecular proton transfer (ESIPT) fluorophore [17] .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Miao and Fang research groups designed fluorescent nanofilm based sensor for methanol detection. [16] Effective discrimination of methanol, ethanol and propanol is reported using excited-state intramolecular proton transfer (ESIPT) fluorophore. [17] Introduction of electron donor-acceptor (DÀ A) units on AIE fluorophore systems experience the fine-tuning the energy levels of their ground and excited states as well as modify the intramolecular charge transfer (ICT) process, resulting noteworthy wavelength-shifting in emission/absorption spectra.…”
Section: Introductionmentioning
confidence: 99%